GAMBARAN TINGKAT PENGETAHUAN PENATALAKSANAAN DIABETES MELITUS - Desnita Fitri (Jurnal Nurse, 2021)
The increasing number of people with diabetes mellitus can cause health problems for the community which can be caused by various factors, namely lack of knowledge. One of the efforts to reduce health problems is by increasing public knowledge about diabetes mellitus. Knowledge is a very important factor in determining the behavior of DM sufferers towards the disease they are experiencing. Knowledge is behavior based on a better knowledge than that which is not based on knowledge. For DM patients with good knowledge, they can find out how to prevent DM by managing DM to prevent complications. DM management consists of 3 pillars, namely dietary compliance, physical activity and regular medication. In the results of the study, the respondents' characteristics were mostly at the age of 46-55 years or old age, then the gender of the respondents was more in the female sex, and the education level of the respondents was more at the elementary education level. The results show that the respondents' knowledge is more on less knowledge, namely 23 people out of 30 respondents and more than 20 respondents out of 30 respondents do not comply with DM management.